2016
DOI: 10.1007/s10897-016-9999-9
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Anticipated Decision Making around Type 2 Diabetes Genetic Testing: the Role of Scientifically Concordant and Discordant Expectations

Abstract: Type 2 diabetes mellitus (T2DM) genetic testing is undergoing clinical trials to measure the efficacy of genetic counseling for behavior-based risk reduction. The expectations patients bring to the testing process may play an important role in individual outcomes. We conducted a qualitative exploration of anticipated decision-making and expectations around T2DM genetic testing. Semi-structured interviews were completed with Mexican Americans (n = 34), non-Hispanic Black Americans (n = 39), and non-Hispanic Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Other people would be uncomfortable with researchers knowing parts of themselves called Bgenes^(which could be a nebulous concept, although tied with heredity), and they would be concerned that researchers could take advantage of them or the community in some unknown ways. These concerns were raised in other studies (Buseh et al 2013a and2013b;Carmichael et al 2016;Dash et al 2014;George et al 2014;Hamilton et al 2016;Sanderson et al 2013;Schulz et al 2003;Sterling et al 2006;Underwood et al 2013). Participants' inability to articulate what potential dangers might lie ahead is understandable; without specific results, without historical context, and without experience with genomics results, it can be difficult to imagine what kinds of consequences could arise, what significance these could have for individuals and the community, and how individuals and the community might react.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Other people would be uncomfortable with researchers knowing parts of themselves called Bgenes^(which could be a nebulous concept, although tied with heredity), and they would be concerned that researchers could take advantage of them or the community in some unknown ways. These concerns were raised in other studies (Buseh et al 2013a and2013b;Carmichael et al 2016;Dash et al 2014;George et al 2014;Hamilton et al 2016;Sanderson et al 2013;Schulz et al 2003;Sterling et al 2006;Underwood et al 2013). Participants' inability to articulate what potential dangers might lie ahead is understandable; without specific results, without historical context, and without experience with genomics results, it can be difficult to imagine what kinds of consequences could arise, what significance these could have for individuals and the community, and how individuals and the community might react.…”
Section: Discussionmentioning
confidence: 91%
“…The majority of Hmong study participants stated they would be willing to join genomics research projects and surmised that others would be also, including having blood drawn, analyzed, and stored for future testing, because genomic tests could benefit the research subjects as well as the Hmong community. Exploratory research done with other under-represented minorities have also identified a desire for some members to participate, including African Americans (Buseh et al 2013a;Carmichael et al 2016;Dash et al 2014;Halverson and Ross 2012;Sanderson et al 2013;Sussner et al 2011;Underwood et al 2013), African immigrants (Buseh et al 2013b), Hispanics/Latinos (Carmichael et al 2016;Hamilton et al 2016;Sandberg et al 2015;Sanderson et al 2013;Sussner et al 2009) and Cantonese-speaking Chinese Americans (Tong et al 2014). Participants asserted that most Hmong people would want their individual results and not just aggregated results, a desire expressed by other populations (Buseh et al 2013a;Carmichael et al 2016;Hamilton et al 2016;Sanderson et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that Latinx populations were more likely to express concerns about unfair treatment or insurance discrimination (Glenn et al, 2012;Hall et al, 2005;Hamilton et al, 2016;Sussner et al, 2013Sussner et al, , 2015, and were marginally more concerned about GT misuse and more doubtful that physicians would maintain confidentiality when compared to NHW (based on a survey of agreement that "information from GT is likely to be misused") (Rajpal et al, 2017;Singer et al, 2004;Suther & Kiros, 2009). In contrast, other studies found no differences between concerns about discrimination among Latinx and NHW respondents or that greater Latinx insurance-discriminationrelated concerns lost significance in regression models that adjusted for income and education, suggesting socioeconomic confounders (Carmichael et al, 2017;Hall et al, 2005). One study found that Latina respondents reported no concerns about HBOC GT risks while other groups reported four or more.…”
Section: Barriersmentioning
confidence: 96%
“…Studies underscored reasons, like other patient populations, that Latinx patients reportedly would undergo GT: improved prevention and early detection, to inform medical management, to inform children and other family members, to know recurrence risks or guide family planning, because a physician recommended it, and to seek reassurance (typically, that their fetus was healthy). The prospect of disease prevention or other health-related utility, like treatment decisionmaking, was salient (Carmichael et al, 2017;Catz et al, 2005;Glenn et al, 2012;Hurtado-de-Mendoza et al, 2018;Palmer et al, 2008Palmer et al, , 2009Steinberg et al, 2007;Vicuña et al, 2018;Witt et al, 1996).…”
Section: Facilitators or Motivators To Gtmentioning
confidence: 99%
See 1 more Smart Citation